Incorporating shared savings programs into primary care: from theory to practice. Issue 1 (June 2015) - Hayen, Arthur; van den Berg, Michael; Meijboom, Bert; Struijs, Jeroen; Westert, Gert
Abstract Background In several countries, health care policies gear toward strengthening the position of primary care physicians. Primary care physicians are increasingly expected to take accountability for overall spending and quality. Yet traditional models of paying physicians do not provide adequate incentives for taking on this new role. Under a so-called shared savings program physicians are instead incentivized to take accountability for spending and quality, as the program lets them share in cost savings when quality targets are met. We provide a structured approach to designing a shared savings program for primary care, and apply this approach to the design of a shared savings program for a Dutch chain of primary care providers, which is currently being piloted. Methods Based on the literature, we defined five building blocks of shared savings models that encompass the definition of the scope of the program, the calculation of health care expenditures, the construction of a savings benchmark, the assessment of savings and the rules and conditions under which savings are shared. We apply insights from a variety of literatures to assess the relative merits of alternative design choices within these building blocks. The shared savings program uses an econometric model of provider expenditures as an input to calculating a casemix-corrected benchmark. Results The minimization of risk and uncertainty for both payer and provider is pertinent to the design of a shared savings program. In that respect, the primary care setting provides a number of unique opportunities for achieving cost and quality targets. Accountability can more readily be assumed due to the relatively long-lasting relationships between primary care physicians and patients. A stable population furthermore improves the confidence with which savings can be attributed to changes in population management. Challenges arise from the institutional context. The Dutch health care system has a fragmented structure and providers are typically small in size. Conclusion Shared savings programs fit the concept of enhanced primary care. Incorporating a shared savings program into existing payment models could therefore contribute to the financial sustainability of this organizational form.